RECURRENT RUMINAL BLOAT IN A NEONATAL CROSSBRED CALF – A CASE OF RUMINAL DRINKER DUE TO ESOPHAGEAL GROOVE DYSFUNCTION AND ITS MANAGEMENT - C. Jayanthy; C.S. Arunaman; G. Vijayakumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Esophageal groove dysfunction is a fatal cause in neonatal calves if unattended at the early stage. In healthy suckling calves the milk should bypass the rumen and reticulum and enter abomasum which is the true stomach for enzymatic digestion of milk protein. In esophageal groove dysfunction the milk enters rumen where fermentation due to microbes leads to high accumulation of gas hence abdominal distension which proves fatal to the calf. An eight days old female crossbred calf solely on dam’s milk was presented with left sided abdominal distension. On clinical examination the case was diagnosed to be a ruminal drinker due to esophageal groove dysfunction. The calf was relieved of gas by passing atraumatic flexible stomach tube and oral antibiotic to control bacterial fermentation. The calf was weaned gradually from dam’s milk and allowed to feed with the Dam for rumen flora inoculation and early initiation of concentrate and roughage feeding. The calf was free of ruminal bloat post treatment.